A Review on Robust Artificial Neural Network Forecasting Models towards Outliers Problem - Azura Md Ghani, Nor; Bin Ahmad Kamaruddin, Saadi; Hashim, Hishamuddin (International Journal of Engineering and Technology, 2019)
Neurocomputing have been adjusted in time arrangement estimating field, however the nearness of exceptions that for the most part happen in information time arrangement might be hurtful to the information organize preparing. This is on the grounds that the capacity to consequently discover any examples without earlier suppositions and loss of all inclusive statement. In principle, the most well-known preparing calculation for backpropagation calculations inclines toward lessening ordinary least squares estimator (OLS) or all the more particularly, the mean squared error (MSE). In any case, this calculation is not completely hearty when exceptions exist in preparing information, and it will prompt false estimate future esteem. In this paper, the effect of time series outliers in backpropagation training is discussed. The comparisons and related issues of autoregressive moving average (ARIMA) to artificial neural network (ANN) are also discussed briefly in this paper. Moreover, the background of the basic backpropagation neural network (BPNN) time series models; nonlinear autoregressive (NAR) and nonlinear autoregressive moving average (NARMA), is also discussed in this paper. The critical part of the paper is the application of metaheuristics algorithms, mainly the Firefly Algorithm (FFA) to improve the backpropagation models. There are also highlights of latest research works on the robustification of backpropagation using modern optimization algorithms.Â Â